Maturation of flaviviruses starts from one or more icosahedrally independent nucleation centres - Pavel Plevka (2018)
Flaviviruses assemble as fusion-incompetent immature particles and subsequently undergo conformational change leading to release of infectious virions. Flavivirus infections also produce combined mosaic particles. Here, using cryo-electron tomography, we report that mosaic particles of dengue virus type 2 had glycoproteins organized into two regions of mature and immature structure. Furthermore, particles of a maturation-deficient mutant had their glycoproteins organized into two regions of immature structure with mismatching icosahedral symmetries. It is therefore apparent that the maturation-related reorganization of the flavivirus glycoproteins is not synchronized across the whole virion, but is initiated from one or more nucleation centres. Similar deviation from icosahedral symmetry might be relevant to the asymmetrical mode of genome packaging and cell entry of other viruses. © 2011 European Molecular Biology Organization.